The mechanism of Epimedin B in treating osteoporosis as revealed by RNA sequencing‐based analysis. Issue 6 (7th October 2021) - Diao, Xinyue; Wang, Liwen; Zhou, Yating; Bi, Yanan; Zhou, Kun; Song, Lei
Abstract: With the ageing of populations, the management of osteoporosis is a priority of society in general. Epimedin B, a major ingredient of Herba Epimedii, which has the advantages of high content and hypotoxicity has been proved to be effective in preventing osteoporosis in vitro. However, the efficacy and mechanism of Epimedin B on osteoporosis in vivo have not been well elucidated yet. This study aimed to investigate the effects and the potential mechanisms of 8‐week repeated oral administration of Epimedin B (10 and 20 mg/kg/day) on a mouse osteoporosis model. Effects of Epimedin B were evaluated by examinations of serum bone turnover markers, bone mineral density, bone microstructure parameters and histopathological section. Epimedin B significantly rose N‐terminal propeptide of type I procollagen (P1NP) and dropped C‐telopeptide of type I collagen (CTX1). Connectivity density (Conn.D) increased significantly while structure model index (DA) decreased significantly after treated by Epimedin B. Meanwhile, Epimedin B administration significantly increased the number of trabecular bones while significantly decreased the gap between them. Overall, Epimedin B showed beneficial effects on osteoporosis. Furthermore, RNA sequencing‐based analysis revealed 5 significantly down‐regulated transcripts and 107 significantly up‐regulated transcripts between the Epimedin B administration group and the model group. These transcripts were mapped to 15 pathways by KEGG enrichment analysis, of which PI3K‐Akt signalling pathway, MAPK signalling pathway and PPAR signalling pathway were most connected to osteoporosis. To conclude, Epimedin B is effective in treating osteoporosis in mice via regulating PI3K‐Akt, MAPK and PPAR signalling pathway.